Pregnant women's experiences of well-being in high-risk pregnancy: A qualitative study - Kobra Mirzakhani; Abbas Ebadi; Farhad Faridhosseini; Talat Khadivzadeh (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Physical changes in high-risk pregnancy (HRP) can lead to changes in mood and social relationships and negative effects on women's well-being. Individuals in different sociocultural contexts have different perceptions of well-being. Yet, there is limited information about perceptions of well-being in HRP. This study aimed to explore the Iranian women's experiences of well-being in HRP. MATERIALS AND METHODS: This qualitative study was conducted in 2019-2020 through directed content analysis based on the conceptual framework of well-being in HRP. Participants were 26 women with HRP purposively recruited from public and private healthcare settings in Mashhad, Iran. Face-to-face semistructured interviews were held for data collection until data saturation. Data were analyzed through directed content analysis proposed by Elo and kyngäs (2008) and were managed using the MAXQDA (v. 10) program. RESULTS: Well-being in HRP had seven attributes in the five main dimensions of physical, mental-emotional, social, marital, and spiritual well-being. The seven attributes of well-being in HRP were controlled physical conditions, controlled mood, emotions, and affections, perceived threat, self-efficacy, and competence for multiple role performance, maintained social relationships, meaning seeking and relationship with the Creator, and positive marital relationships. CONCLUSION: The present study provide an in-depth understanding about well-being in the Iranian women with HRP. It is a complex and multidimensional concept with physical, mental-emotional, social, marital, and spiritual dimensions. Comprehensive multicomponent interventions are needed to promote well-being among women with HRP and designed the guidelines to provide woman-centered care.